Successful mRNA SARS-Cov-2 vaccine rechallenge after a first episode of immune thrombocytopenic purpura. (19th May 2022) - Chanut, Mathilde; Jaidi, Rym; Kohn, Milena; Grange, Thomas; Brones, Clara; Lombion, Naëlle; Rousselot, Philippe; Longval, Thomas
Abstract: In 2021, the world experienced the most extensive vaccination campaign to defeat COVID-19. Many cases of idiopathic thrombocytopenia have been reported following injections of SARS-Cov-2 mRNA vaccine. We present the case of a 73-year-old woman with de novo ITP after a first injection of SARS-Cov-2 mRNA vaccine (Moderna vaccine) who experienced a successful rechallenge of SARS-Cov-2 mRNA vaccine (Pfizer vaccine) a few months later.